Ketangguhan Pribadi Orang tua Tunggal : Studi Kasus pada Perempuan Pasca Kematian Suami - Dara Nurfitri; Siti Waringah (Gadjah Mada Journal of Psychology (GamaJoP), 2018)
Losing a husband due to death causes feelings of griefs and raises some problems. It changes the status of women became a single parent. The aims of this study were to understand what caused single parents to own hardiness and how the hardiness was able to help them rising up from the critical period after their husbands died. This study used a qualitative method with a case study research. Informants were three single parents and three significant others. This study used an in-depth semi-structured interview for data collection. The results showed that the three informants were able to rise above the critical period after their husbands died and survived as single parents. This happened because all the informants had hardiness. The effort and time required for the informants to rise were different. Three factors that gave contribution to increasing hardiness were mastery experiences, feelings of positivity, and parental explanatory styles.